POWER RELATIONS OF NON-NATIVE ENGLISH TEACHERS AND THEIR STUDENTS IN THE CLASSROOM - Sudar, Sudar (Jurnal Penelitian Humaniora, 2013)
The current study deals with the Power Relations between non-native English teachers and their students in the classroom. The objectives of the study is to describe the Power Relations between non-native English teachers and their students in the classroom. The data are in the form of utterances showing Power Relations which are taken from nine senior high schools in Purworejo. The researcher used the critical discourse analysis to analyze the data. The research results are as the follows: (1) in term of message units performance, non-native English teachers were more powerful than their students; (2) in five senior high schools non-native English teachers and their students performed turn distribution equally; (3) in performing the initiation, non-native English teachers are more powerful than their students; (4) the initiation of discussion topic was fully done by non-native English teachers; (5) non-native English teachers and their students had equal right to response; (6) the determination of turn-taking activities was mostly performed by non-native English teachers. In conclusion, non-native English teachers iunder the study were more powerful than their students in the classroom. It was much influenced by Indonesian culture.